2005
DOI: 10.1111/j.1399-6576.2005.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

The pre‐emptive analgesic effect of intra‐articular bupivacaine in arthroscopic knee surgery*

Abstract: Background:  The purpose of this study was to determine whether intra‐articular injection of bupivacaine prior to surgery provided better pain control after arthroscopic meniscectomy as compared with post‐operative administration of bupivacaine. Methods:  Forty patients of American Society of Anesthesiologists (ASA) class I or II undergoing arthroscopic meniscectomy were assigned in a randomized, double‐blinded manner into two groups: Group I received 20 ml of 2.5 mg/ml bupivacaine without epinephrine 30 min b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
0
18
0
2
Order By: Relevance
“…Intra-articular injections of analgesics following knee surgery have been shown to reduce requirements for postoperative pain medication and lead to earlier discharge from the hospital. 5,6 The intraperitoneal instillation of local anesthetic has similarly been shown to decrease postoperative pain following laparoscopic cholecystectomy. 7,8 Parker et al 9 were the first to evaluate whether the periprosthetic administration of a local anesthetic was effective in improving patients' postoperative course following subpectoral breast augmentation.…”
mentioning
confidence: 98%
“…Intra-articular injections of analgesics following knee surgery have been shown to reduce requirements for postoperative pain medication and lead to earlier discharge from the hospital. 5,6 The intraperitoneal instillation of local anesthetic has similarly been shown to decrease postoperative pain following laparoscopic cholecystectomy. 7,8 Parker et al 9 were the first to evaluate whether the periprosthetic administration of a local anesthetic was effective in improving patients' postoperative course following subpectoral breast augmentation.…”
mentioning
confidence: 98%
“…Post‐operatively, there was no longer a significant analgesic effect of pre‐operative bupivacaine. Therefore a prolonged post‐operative benefit, as hypothesized in the beginning of the study and previously shown in humans (Tuncer et al. 2005), could not be demonstrated.…”
Section: Discussionmentioning
confidence: 81%
“…Despite the clear theoretical benefit of pre‐emptive analgesia (Dahl & Kehlet 1993), contradictory results about the optimal timing of the intra‐articular bupivacaine administration have been reported in humans. Tuncer et al. (2005) demonstrated that pre‐operative administration was superior to post‐operative while Fagan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Bupivacaine was tested intra-articularly before and after knee arthroscopy, with better results in controlling pain when administered before surgery, suggesting a preemptive effect 40 . Because ketamine has been reported as effective in controlling postoperative hyperalgesia, it could also be used before the procedure to evaluate a possible preemptive action, as well as pain could be evaluated weeks after surgery to test its effect on chronic pain after surgery.…”
Section: Discussionmentioning
confidence: 99%